Pengaruh Gaya Kepemimpinan Transaksional terhadap Komitmen Organisasional di Industri Layanan Publik (The Influence of Transactional Leadership Style on Organizational Commitment in the Public Service Industry) - Nur Habibah Angkat; Yulinda Yulinda; Angga Hade Fahrezi; Albalkhy Yahya Sinuraya; Ramadan Pasaribu (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Leadership in public service organizations plays a crucial role in shaping employee behavior and work attitudes. One of the leadership styles widely applied in this sector is transactional leadership, which focuses on reward and punishment systems in managing performance. This study aims to examine the influence of transactional leadership style on organizational commitment among employees in the public service industry. Using a qualitative descriptive approach through literature review, this article synthesizes theories and findings from various relevant previous studies. The results indicate that transactional leadership style can positively influence organizational commitment, especially when applied fairly and consistently. This research provides insight that structured leadership can strengthen employee loyalty toward the organization, particularly in work environments that emphasize formal rules and accountability.